The Influence of the Meronce Method on Children's Cognition and Creativity at SDN 40 Mandau - Andriani, Andriani (Journal of English Language and Education, 2025)
This study aims to analyze the effect of meronce method on students’ cognitive and creativity at SDN 40 Mandau. The background of this research is based on the low cognitive and creativity of students. This research employed a quasi-experimental method with a pretest-posttest control group design. The research subjects consisted of two groups with a total of 40 children as subjects at the elementary school level of grade III at SDN 40 Mandau, namely the experimental group treated with the meronce method and the control group using the drawing method. The research instruments were in the form of cognitive tests and observation sheets, which were analyzed using parametric statistical tests (t-tests) to determine the differences in cognitive and creativity between the two groups. The results of the analysis showed a statistically significant difference between the experimental group and the control group, with students in learning using meronce method showed a higher increase in cognitive and creativity abilities. Therefore, it can be concluded that the application of the meronce method has a positive and significant effect on enhancing students' cognitive and creativity at SDN 40 Mandau.